Hearing Aid Effect on Elderly\'s Depression in Tehran\'s Nursing Homes - Reza Hosienabadi; Khosro Goorabi; Hosien Shareh (University of Social Welfare & Rehabilitation Sciences, 2007)
Objectives: Moderate hearing impairment in older age can affect physical and psychosocial health of people. The rate of isolation, lack of self confidence, depression and probably dementia in this people is high. This study was conducted to study the hearing aid effect on older adults depression in tehran nursing homes. Methods & Materials: In this study depression was assessed in 3 groups of older adults: 30 normal hearing older adults, 30 hearing impaired older adults without hearing aid and 20 hearing impaired older adults with hearing aid. Beck depression inventory (ii) was used to assess depression. For analyzing data one way anova was used. Results: Mean scores in bdi was 11.43, 21.53, 16.40 for groups. The difference between groups was significant. Correlation between age and depression was significant in 1 and 3 groups. Conclusion: It seems that hearing aid use is effective in decreasing depression in older adults.